Bringing Health Policy Issues Front and Center in the Community: Expanding the Role of Community Health Coalitions - Joel S. Meister, PhD; Jill Guernsey de Zapien (Centers for Disease Control and Prevention, 2005)
Background Systemic, environmental, and socioeconomic conditions create the context in which community members deal with their health concerns. Comprehensive, community-based chronic disease prevention interventions should address community-wide or regional policy issues that influence lifestyle behaviors associated with chronic diseases. Context In two communities along the Arizona-Mexico border, community coalitions that administered a comprehensive diabetes prevention and control intervention expanded their membership to become policy and advocacy coalitions with broad community representation. These coalitions, or Special Action Groups (SAGs), identified and prioritized policy issues that directly or indirectly affect physical activity or nutrition. Methods Local schools were one focus of advocacy. The Centers for Disease Control and Preventions School Health Index was implemented as part of the overall intervention; the SAGs supported schools in advocating for more physical education programs, removal of vending machines, substitution of more healthful options in vending machines, and changes in health education curricula. In the broader community, the SAGs promoted opportunities for walking and bicycling, long-term planning by their cities and counties, and healthy food choices in local grocery stores. Advocacy tactics included attending and making presentations at city council, school board, parks and recreation, and planning and zoning commission meetings; participating on long-range planning committees; organizing an annual community forum for elected and appointed officials; and presenting healthy food and cooking demonstrations in local markets. Consequences After three years, SAGs were able to document changes in local policies and practices attributable to their activities. Interpretation The SAGs contributed to systems changes in their communities and were able to obtain new resources that support protective behaviors. Also, the advocacy process itself provided strong positive reinforcement to all participants in this comprehensive diabetes intervention.